Clinical heterogeneity of feeding and eating disorders: using personality psychopathology to differentiate “simplex” and “complex” phenotypes - Marco Colizzi; Carla Comacchio; Marco Garzitto; Lavinia Bucciarelli; Anna Candolo; Maddalena Cesco; Veronica Croccia; Alessandra Ferreghini; Rosita Martinelli; Alessandra Nicotra; Giulia Sebastianutto; Matteo Balestrieri (BMC Psychiatry)
Abstract Background To investigate Feeding and Eating Disorders (FED) heterogeneity based on the co-occurrence of FED symptoms and personality psychopathology, on the hypothesis that empirical profiles would not confirm current FED categories but identify unique phenotypes carrying different levels of clinical complexity. Methods Latent Profile Analysis profiled FED patients based on the assessment of both FED symptoms, through the Eating Disorders Inventory, third version (EDI-3), and personality characteristics, through the Minnesota Multiphasic Personality Inventory-2. Then, profiles were compared across socio-demographic and clinical characteristics. Results Among 109 eligible patients, three FED profiles were identified: (i) FED simplex (low eating symptoms, absence of dysfunctional personality); (ii) FED simplex-severe (high eating symptoms only); and (iii) FED complex-severe (high eating symptoms and dysfunctional personality). Despite an uneven distribution (χ2(6) = 15.20, adjusted-p = 0.029), FED profiles did not unequivocally confirm clinical diagnoses (e.g., Anorexia Nervosa). A difference in Body Mass Index (BMI) was observed (K(2) = 15.06, adjusted-p = 0.001), but lower BMI did not identify the most severe group. Profiles differed in EDI-3 overall scores (e.g., Eating Disorder Risk Composite: K(2) = 43.08, adjusted-p < 0.001), Body Uneasiness Test Global Severity Index (GSI: K(2) = 29.33, adjusted-p < 0.001), Binge Eating Scale severity (K(2) = 25.49, adjusted-p < 0.001), number of psychiatric (K(2) = 8.79, adjusted-p = 0.021) and personality diagnoses (K(2) = 11.86, adjusted-p = 0.005), and Symptom Checklist-90-Revised GSI (F(2,103) = 37.68, adjusted-p < 0.001), with FED complex-severe patients being generally the most severely impaired in terms of FED symptoms, body concerns, depersonalization, and psychiatric comorbidities. Conclusions Findings support the hypothesis of distinguishing FED simplex and complex phenotypes, based on the co-occurrence of dysfunctional personality, with implications for FED severity and clinical practice.